Soluble or soluble/membrane TNF-± inhibitors protect the brain from focal ischemic injury in rats (2015)
Tumor Necrosis Factor-alpha (TNF-α) is an immunomodulatory and proinflammatory cytokine implicated in neuro-inflammation and neuronal damage in response to cerebral ischemia. The present study tested the hypothesis that anti-TNF-α agents may be protective against cerebral infarction. Transient focal ischemia was artificially induced in anesthetized adult male Wistar rats (300–350 g) by middle cerebral artery occlusion (MCAO) with an intraluminal suture. TNF-α function was interfered with either a chimeric monoclonal antibody against TNF-α (infliximab-7 mg/kg) aiming to TNF-α soluble and membrane-attached form; or a chimeric fusion protein of TNF-α receptor-2 with a fragment crystallizable (Fc) region of IgG1 (etanercept-5 mg/kg) aiming for the TNF-α soluble form. Both agents were administered intraperitoneally 0 or 6 h after inducing ischemia. Infarct volume was measured by 2,3,5-triphenyltetrazolium chloride staining. Cerebral infarct volume was significantly reduced in either etanercept or infliximab-treated group compared with non-treated MCAO rats 24 h after reperfusion. These results suggest that anti-TNF-α agents may reduce focal ischemic injury in rats.